Effect Of Work Life Balance In Improving Teacher Performance at SD IT Al-Khattaaby - Tairas, Maudi Dian; Sampetan, Suparni; Sukri, Sukri (Perkumpulan Dosen Muda (PDM) Bengkulu, 2025)
Purpose: This study aims to analyze the effect of work-life balance on teacher performance at SD IT Al-Khattaaby. The main focus of this study is how the balance between professional and personal life can improve teaching effectiveness and teacher welfare. Methodology: This study uses a quantitative approach with a survey method. Data were collected through an online questionnaire filled out by 30 teachers, and analyzed using multiple linear regression to test the relationship between work-life balance and teacher performance. Results:Â The findings show a significant positive relationship between work-life balance and teacher performance. Regression analysis shows that every one-unit increase in work-life balance is correlated with an increase in teacher performance of 0.959. Findings: Work-life balance has been shown to play an important role in increasing teacher motivation, job satisfaction, and engagement in the work environment. Novelty and Originality: This study contributes to the academic literature by examining the relationship between work-life balance and teacher performance in the context of Islamic education in Indonesia, an area that remains under-explored in global studies. Conclusion:Â Schools need to develop policies that support work-life balance, such as flexible working hours and teacher well-being programs, to improve performance sustainably.Â Type of Paper: Research Article